Effect of galactose-depleted and intact xyloglucan intake on glucose and lipid metabolism in diet-induced obese mice - Seiichiro Aoe; Michiko Kato; Kazuhiko Yamatoya (Journal of Functional Foods, 2024)
This study investigated the effects of galactose-depleted xyloglucan derived from tamarind seed gum (GXG-TG) on glucose and lipid metabolism in diet-induced obese mice by comparison with intact xyloglucan (TG). Twenty-four male C57BL/6J mice were fed a high-fat diet containing 3 g/100 g of either GXG-TG or TG for 12 weeks. Reduction of postprandial glucose rise was observed in the TG group compared to the control, whereas the GXG-TG group showed intermediate values. Serum cholesterol levels and hepatic mRNA expression of HMG-CoA reductase were significantly lower in the GXG-TG and TG groups compared to the control, while there was no increase in cecal short chain fatty acids in the GXG-TG or TG group. These results indicated that GXG-TG was converted to insoluble dietary fiber and maintained the serum cholesterol-lowering effect, although the blood glucose level-lowering effect was attenuated. TG, although moderately viscous, improved glucose tolerance and lipid metabolism in diet-induced obesity model mice.